READING AS AN IMPORTANT SKILLS FOR STUDENTS - Maryati Salmiah (UIN Sumatera Utara, 2017)
Language is a very essential instrument in communication. According to Oxford Advanced Learners Dictionary of Current English, language is “(1)The system of sounds and words used by humans to express their thoughts and feelings, (2) the particular language system used by a people or nation” (Hornby, 1995). It means people can express their ideas, thoughts, feelings, and desires by language. People have to learn language and master four basic language skills. They are listening, speaking, reading, and writing. The four basic language skills are divided into two media for language communication: 1) receiving the message, i.e.,reading and listening, 2) and sending the message, i.e., speaking and writing. These skills are used for completing communication when people learn about language.